Selective grazing by cattle on spatially and seasonally heterogenous rangeland in Sahel - Ayantunde, Augustine A.; Hiernaux, Pierre H.Y.; Fernández Rivera, S.; Keulen, H. van; Udo, H.M.J. (Elsevier, 1999)
The selective use by cattle of range resources in the Sahel was assessed in terms of quantity and nutritional quality of the herbage grazed and diet selected. Peak standing crop was 1951 kg ha -1 dry matter (DM) with 47.9 kg nitrogen (N) ha-1 and 7.4 kg phosphorus (P) ha -1. Esophageally fistulated cattle diets were consistently (p<0.05) higher in N, P and organic matter digestibility (OMD) than the herbage grazed. Cattle consumed 48 percent of the mean annual herbage production. The results indicate grazing ruminants select a higher quality diet from Sahelian rangelands than can be predicted on the basis of pasture evaluation alone. Therefore, the foraging behaviour of the animals needs to be considered in the evaluation of Sahelian rangelands for animal production.